Growth performance and bone characteristics of broiler chickens fed corn-soy diet supplemented with different levels of vitamin premix and sources of mineral premix. (2019) - Ao, T.; Paul, M.A.; Pescatore, A.J.; Macalintal, L.M.; Ford, M.J.; Dawson, K.A.
Summary: Inorganic trace mineral salts in the premix have a detrimental effect on the stability of vitamins due to redox reactions. A study was conducted to investigate the effect of dietary supplementation of different levels of vitamin premix with different mineral premixes on the performance and bone characteristics of broilers. A 2 x 2 factorial dietary treatment was used with two levels of vitamins and two types of minerals in the premix. A total of 1056, one-day old chicks were randomly assigned to four dietary treatments with 12 replicate pens of 22 chicks for 28 d. An interactive effect between vitamin levels and mineral sources on weight gain and feed intake of chickens was detected. Chickens fed the diet containing 100% vitamin premix with either source of mineral premix had higher (P < 0.01) weight gain and feed intake than those fed the diet containing 30% vitamin premix with either source of mineral premix. However, the chickens fed the diet containing the 30% vitamin premix with the organic minerals had higher (P < 0.01) weight gain and feed intake than those fed the diet containing 30% vitamin premix with inorganic minerals. Chickens fed the diet containing organic mineral premix had lower (P < 0.05) mortality and feed to gain ratio and higher (P < 0.01) bone breaking strength and ash content of tibia than those fed the inorganic mineral premix treatment. Chickens fed the diet containing 100% vitamin premix had higher (P < 0.01) breaking strength of femur and tibia ash than those fed the diet containing 30% vitamin premix. The results from this trial indicated that total replacement of inorganic trace minerals with organic minerals can increase the storage stability of vitamins in feed premixes containing both vitamins and trace minerals, which is reflected in better growth performance in poultry.